PENGARUH KOMITMEN ORGANISASI, KEINGINAN SOSIAL, DAN ASIMETRI INFORMASI TERHADAP HUBUNGAN ANTARA PARTISIPASI PENGANGGARAN DENGAN KINERJA MANAJER - Supriyono, R. A. Supriyono (Journal of Indonesian Economy and Business, 2005)
This study investigates the influence of organizational commitment, social desirability,and information asymmetry on the relationship between budgeting participation andmanager performance. The previous results of such relationship indicate inconsistency. Tounderstand such relationship contingency approach is needed. Contingency approach is anidea that such relationship is suspected to be influenced by various factors or variableswhich are conditional and called moderating variables. This study analyzes the influence oforganizational commitment, social desirability, and information asymmetry on therelationship between budgeting participation and manager performance.To test such relationship survey questionnaires are used. The questionnaires were sentto the manager of goi public companies in Jakarta Stock Exchange (JSX). Moderatingregression analysis (MRA) was applied to test the objective of the research. The test resultsindicate that: (1) budgeting participation and manager performance have positiverelationship and statistically significant, (2) organizational commitment, social desirability,and information asymmetry has positive and statistically significant influence on therelationship between budgeting participation and manager performanceKeyword: budgeting participation, organizational commitment, social desirability, information asymmetry, and manager performance.